(untitled) (Research, Society and Development, 2021)
The objective of the study was to evaluate the antioxidant effect of the hydroethanolic extract of liana-thousand-men (Aristolochia tringularis Cham.), In in vitro tests with erythrocytes from individuals with neurodegenerative disease, through the evaluation of oxidative biomarkers and enzymatic antioxidants and not enzymatic. The analysis of the total phenolic compounds of the stems of vine-thousand-men, from the city of Panambi- RS, was carried out. Subsequently, in vitro tests were carried out, through treatment with different concentrations of the plant extract (0.025; 0.050; 0.100 and 0.200 mg / mL). Afterwards, TBARS, CAT, GSH and GST levels were analyzed. In the dosage of total phenolic compounds, the value of 426mg / mL was obtained. In the oxidative stress assessments, it was possible to observe an increase in lipoperoxidation at concentrations of 0.050mg / mL and 0.200mg / mL, with emphasis on the concentration of 0.050mg / mL, where the damage in lipids was more significant. There was no significant change in GSH levels at any of the extract concentrations used in the study. The activity of the catalase enzyme was shown to be reduced at a concentration of 0.100 mg / mL. There was a decrease in GST at concentrations of 0.100 and 0.200mg / mL, thus impairing the endogenous antioxidant action. Thus, the hydroethanolic extract of vine-thousand-men did not have an antioxidant effect, but a toxic effect at these concentrations.